Ammonia‐weighted imaging by chemical exchange saturation transfer MRI at 3 T. (5th July 2018) - Zöllner, Helge Jörn; Butz, Markus; Kircheis, Gerald; Klinker, Stefan; Häussinger, Dieter; Schmitt, Benjamin; Schnitzler, Alfons; Wittsack, Hans‐Jörg
Abstract : Hepatic encephalopathy (HE) is triggered by liver cirrhosis and is associated with an increased ammonia level within the brain tissue. The goal of this study was to investigate effects of ammonia on in vitro amide proton transfer (APT)‐weighted chemical exchange saturation transfer (CEST) imaging in order to develop an ammonia‐sensitive brain imaging method. APT‐weighted CEST imaging was performed on phantom solutions including pure ammonia, bovine serum albumin (BSA), and tissue homogenate samples doped with various ammonia concentrations. All CEST data were assessed by magnetization transfer ratio asymmetry. In addition, optical methods were used to determine possible structural changes of the proteins in the BSA phantom. In vivo feasibility measurements were acquired in one healthy participant and two patients suffering from HE, a disease associated with increased brain ammonia levels. The CEST effect of pure ammonia showed a base‐catalyzed behavior. At pH values greater than 5.6 no CEST effect was observed. The APT‐weighted signal was significantly reduced for ammonia concentrations of 5mM or more at fixed pH values within the different protein phantom solutions. The optical methods revealed no protein aggregation or denaturation for ammonia concentrations less than 5mM. The in vivo measurements showed tissue specific and global reduction of the observed CEST signal in patients with HE, possibly linked to pathologically increased ammonia levels. APT‐weighted CEST imaging is sensitive to changes in ammonia concentrations. Thus, it seems useful for the investigation of pathologies with altered tissue ammonia concentrations such as HE. However, the underlying mechanism needs to be explored in more detail in future in vitro and in vivo investigations. Abstract : APT CEST imaging could be used to assess different tissue parameters such as pH or the concentrations of mobile proteins. The current study analyses the sensitivity of APT CEST imaging to ammonia concentrations at a fixed pH level. This indirect ammonia‐weighted contrast allows for the investigation of diseases linked with ammonia alterations such as hepatic encephalopathy.